Metabolic stress leads to divergent changes in the ghrelinergic system in goldfish (Carassius auratus) gonads - Rajeswari, Jithine Jayakumar; Hatef, Azadeh; Golshan, Mahdi; Alavi, Sayyed Mohammad Hadi; Unniappan, Suraj (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2019)
Various endocrine factors that regulate energy homeostasis are also implicated in the reproductive physiology of mammals. However, the hormonal link between metabolism and reproduction in fish is poorly understood. Ghrelin is a multifunctional hormone with both metabolic and reproductive roles in vertebrates. Post-translational acylation by ghrelin-O-acyltransferase (GOAT) is critical for its biological actions. The expression of ghrelin, ghrelin or growth hormone secretagogue receptor (GHSR), and GOAT (which forms the ghrelinergic system) in fish under metabolic stress remains unclear. In this research, we used RT-qPCR and Western blot analysis to determine the expression of the ghrelinergic system in goldfish (during the reproductively active phase) hypothalamus and gonads under 7 and 28 days of fasting. We found a significant increase in preproghrelin mRNA expresson in the ovary, and GOAT mRNA expression in the testis of goldfish deprived of food for 7 days. In fish deprived of food for 28 days, preproghrelin, GHSR and GOAT mRNA expression was significantly increased in the hypothalamus of male goldfish. Such differences were not observed in the hypothalamus of female fish, and in the testis of 28 days fasted fish. Meanwhile, preproghrelin, GHSR, and GOAT expression (both mRNA and protein) was significantly increased in the ovary of female fish fasted for 28 days. Ghrelin has been shown to suppress oocyte maturation in fish. The upregulation of a system that has ovarian inbititory roles suggests a role for ghrelin in maintaining reduced reproductive capability during metabolically challenging periods.
Keywords: omezení příjmu potravy; messenger RNA; Acyltransferases; acyltransferasy; Gonads; zvířata; Goldfish; Fasting; ghrelin; Stress, Physiological; hypothalamus; gonády; fyziologický stres; Animals; Ghrelin; karas zlatý; Hypothalamus; RNA, Messenger